Experimental Study of a System for Hydrogen Permeation from Gas Phase to Liquid Sodium. (1st February 2022) - Brazzale, Pietro; Chassery, Aurélien; Gilardi, Thierry; Latgé, Christian; Meyer, Xuân-Mi; Joulia, Xavier
Abstract: In the framework of sodium fast reactors, the management of tritium contamination in the sodium secondary circuit and the control of its release into the atmosphere is fundamental. In order to capture and recover tritium by coprecipitation worth hydrogen in cold traps, it is necessary to maintain a certain amount of hydrogen dissolved in the liquid sodium stream. Hydrogen injection by permeation through nickel membranes has been proposed to provide a continuous hydrogen intake to a liquid sodium stream, allowing the desired hydrogen concentration to be reached. A permeator prototype and the related process have been designed. Permeation tests have been carried out in an experimental facility set up at CEA Cadarache at sodium temperatures from 375°C to 450°C and hydrogen partial pressures from 5 × 10 3 to 3 × 10 4  Pa in order to quantify their influence on hydrogen permeation flux. Measurements on both the gas and sodium sides provide a complete hydrogen content observability over the system. Experimental results show a good agreement with the theoretical permeation laws for hydrogen pressures below 2 × 10 4  Pa and provide an estimation of the temperature dependency of the permeability coefficient, which will be useful for the industrial scale-up of the process.